Routledge Handbook on the UN and Development (Taylor & Francis, 2020)
Development, Development Challenges, Global Governance, International Relations, Migration, Peace-Building, Sustainable Development Goals, The UN, The World Bank
English
Keywords: International relations; Politics & government; development; development challenges; global governance; international relations; JP; JPS; JPWH; migration; peace-building; sustainable development goals; the UN; the world bank